2017
DOI: 10.1128/aac.01516-17
|View full text |Cite
|
Sign up to set email alerts
|

Changing Antimalarial Drug Sensitivities in Uganda

Abstract: Dihydroartemisinin-piperaquine (DP) has demonstrated excellent efficacy for the treatment and prevention of malaria in Uganda. However, resistance to both components of this regimen has emerged in Southeast Asia. The efficacy of artemether-lumefantrine, the first-line regimen to treat malaria in Uganda, has also been excellent, but continued pressure may select for parasites with decreased sensitivity to lumefantrine. To gain insight into current drug sensitivity patterns, ex vivo sensitivities were assessed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 49 publications
4
56
2
Order By: Relevance
“…Taken together, these results strongly suggest that neither back mutation nor additional mutations in pfcrt was associated with the observed recovery of chloroquine sensitivity in the study area. It is of note that recovery of chloroquine sensitivity after its withdrawal occurred much earlier in Gulu than in other regions in Uganda [9,[22][23][24]41]. In 2013, as much as 65% of parasites displayed ex vivo chloroquine resistance [24] and 60-80% carried K76T allele in Tororo, Eastern Uganda [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results strongly suggest that neither back mutation nor additional mutations in pfcrt was associated with the observed recovery of chloroquine sensitivity in the study area. It is of note that recovery of chloroquine sensitivity after its withdrawal occurred much earlier in Gulu than in other regions in Uganda [9,[22][23][24]41]. In 2013, as much as 65% of parasites displayed ex vivo chloroquine resistance [24] and 60-80% carried K76T allele in Tororo, Eastern Uganda [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, with widespread discontinued use, numerous molecular-epidemiological studies showed that there was return of chloroquine susceptibility in P. falciparum field isolates [4]. This is supported by ex vivo [5][6][7][8][9][10][11][12][13][14][15][16] and in vivo drug-susceptibility studies [5,17,18]. Findings suggest that chloroquine might be re-used in the future as an option for the treatment and/or chemoprophylaxis on the condition that chloroquine sensitivity is maintained in the area.…”
mentioning
confidence: 94%
“…Unexpectedly, in African isolates, amplification of Pfpm2 gene was shown to occur at a much higher frequency (~27% on average across clinical sites in Africa, reaching 30.5% in Burkina Faso and 33.9% in Uganda) than was recently described (from 11.1% to 13.8% in Uganda and 1.1% in Mozambique) (27, 41). Considering the geographical extent and the diversity of the clinical sites in Africa, the high frequency reported at sites distant to each other suggests that amplification of Pfpm2 gene occurred independently in each site.…”
Section: Discussionmentioning
confidence: 66%
“…An evaluation is currently ongoing to see whether, and if so to what extent, these markers of artemisinin and PPQ resistance affected the parasite clearance half-life (PCT1/2) and PCR-adjusted 28 days follow up in patients treated with artefenomel/PPQ (study MMV OZ439 13 003). However, it was recently reported that compared to drug sensitivities measured on Ugandan isolates from 2010 to 2013 (from the same site, namely Tororo), those measured in 2016 to chloroquine, amodiaquine, and PPQ were increased by 7.4, 5.2 and 2.5-fold respectively (41). This longitudinal study showed that rather than drug resistance developing to these three antimalarial drugs, an increase in sensitivity was observed that was correlated with low prevalence of the polymorphisms recently associated with resistance to artemisinins or PPQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation